Automotive handbook - Robert Bosch GmbH (Plochingen : Robert Bosch, 2011)
The 8th edition of the world's definitive automotive technology reference marks Bosch's 125th anniversary. Now significantly updated, this book is a must for engineers working in the car industry. The Automotive Handbook is the flagship publication in the BOSCH handbook series on different automotive technologies; one of the most definitive sets of reference books that automotive engineers have at their disposal, and now translated into 11 different languages. 2011 marks the 125th anniversary for BOSCH, and their longstanding expertise and innovative technologies are documented in this new edition that contains just about anything relevant to automobile design, development and quality engineering. As progress in the field of automotive engineering has grown apace it has expanded from 96 pages in 1936, to 1258 pages today. This new edition is significantly updated, with key changes including more emphasis on electrical systems, and a new chapter on driver assistance systems. Very highly regarded throughout the automotive industry, it is used as a quick easy reference and to deliver the detail necessary for more complex ideas
-- Basic principles of physics -- Quantities and units -- Basic equations used in mechanics -- Vibrations and oscillations -- Acoustics -- Hydrostatics -- Fluid mechanics -- Thermodynamics -- Electrical engineering -- Electronics -- Electrochemistry -- Mathematics and methods -- Mathematics -- Finite-element method (FEM) -- Control engineering -- Materials -- Chemical elements -- Substances -- Materials -- Properties of metallic materials -- Properties of non-metallic materials -- Heat treatment of metallic materials -- Corrosion and corrosion protection -- Deposits and coatings -- Operating fluids -- Lubricants -- Fuels -- Brake fluids -- Coolants -- Machine parts -- Springs -- Slide bearings -- Roller bearings -- Gears and tooth systems -- Belt drives -- Chain drives -- Joining and bonding techniques -- Detachable connections -- Permanent joints -- Vehicle physics -- Basic terms of automotive engineering -- Motor-vehicle dynamics -- Aerodynamics -- Vehicle acoustics -- Internal-combustion engines -- Mixture formation, combustion, emissions -- Gasoline engine -- Diesel engine -- Charge cycle and supercharging -- Reciprocating-piston engine -- Wankel rotary engine-- Engine cooling -- Engine lubrication -- Air filtration -- Turbochargers and superchargers -- Exhaust gas system -- Emission-control and diagnosis legislation -- Exhaust-gas measuring techniques -- Diagnostics -- Management for spark-ignition engines -- Cylinder charge -- Fuel supply -- Mixture formation -- Ignition -- Catalytic exhaust-gas treatment -- Alternative gasoline-engine operation -- LPG operation -- Engines fueled by natural gas -- Management for diesel engines -- Fuel supply system (low-pressure stage) -- Common-rail injection system -- Time-controlled single-cylinder pump system -- Diesel distributor injection pumps -- Start-assist systems -- Exhaust-gas treatment -- Alternative drives -- Hybrid drives -- Fuel cells for the vehicle drive -- Drivetrain -- Chassis systems -- Suspension -- Shock absorbers and vibration absorbers -- Wheel suspensions -- Wheels -- Tires -- Tire-pressure monitoring system -- Steering -- Brake systems -- Brake systems for passenger cars -- Electrohydraulic brake -- Brake systems for commercial vehicles -- Wheel brakes -- chassis control and active safety -- Antilock braking system -- Traction control system -- Driving-dynamics control system -- Integrated driving-dynamics control systems -- Vehicle bodies -- Road-vehicle systematics -- Vehicle bodies, passenger cars -- vehicle bodies, commercial vehicles -- Lighting equipment -- Automotive windshield and window glass -- Windshield, rear-window and headlamp cleaning systems -- Passive safety -- Occupant-protection systems -- Vehicle security systems -- Locking systems -- Theft-deterrent systems -- Automotive electrics -- Vehicle electrical systems -- Starter batteries -- Electrical machines -- Alternators -- Starting systems -- Actuators -- Wiring harnesses and plug-in connections -- Electromagnetic compatibility (EMC) and interference suppression -- Symbols and circuit diagrams -- Automotive electronics -- Automotive software engineering -- Automotive networking -- Buses in motor vehicles -- Architecture of electronic systems -- Sensors -- Mechatronics -- Comfort and convenience -- Passenger-compartment climate control -- Comfort and convenience systems in the door and roof areas -- Comfort and convenience functions in the passenger compartment -- User interfaces, telematics and multimedia -- Display and control -- Radio and TV reception in motor vehicles -- Traffic telematics -- EU recording equipment -- Driver-assistance systems -- Parking systems -- Vehicle navigation -- Adaptive cruise control -- Predictive emergency-braking systems -- Video-based driver-assistance systems -- Night-vision systems -- Appendices -- Technical terms -- Abbreviations
Includes index
Translated from the German
Keywords: Automobiles -- Design and construction -- Handbooks, manuals, etc